Mobilizing the Synergy Potential of Digital Platform in Managerial Education - V. G. Antonov; A. V. Raychenko; V. V. Maslennikov (Вестник Российского экономического университета имени Г. В. Плеханова, 2021)
The article studies modernization of digital platform potential in order to coordinate interaction of practice, science and education in the field of management. The key focus is made on the fact that as a result of digital organization development the role of virtual space becomes prevailing in managers’ work and nearly all traditional methods of management undergo drastic changes. Unique processes of managing digital organizations require revision of methodological approaches to the problem of sustainable development in conditions of digital transformation, which mainly has a turbulent character. It is underlined that the major problem of today’s management is the vague definition of different notions, whose understanding is crucial for managers, who otherwise cannot link digital strategy with their work. The article used materials and findings of fundamental and applied research done by authors within the frames of budget, business and initiative development of innovation, industrial and educational products. Testing of these solutions proved their need in the field of practical management, scientific research and managerial education.